Contribution of microreactor technology and flow chemistry to the development of green and sustainable synthesis - Fanelli, Flavio; Parisi, Giovanna; Degennaro, Leonardo; Luisi, Renzo (Beilstein Journal of Organic Chemistry, 2017)
Microreactor technology and flow chemistry could play an important role in the development of green and sustainable synthetic processes. In this review, some recent relevant examples in the field of flash chemistry, catalysis, hazardous chemistry and continuous flow processing are described. Selected examples highlight the role that flow chemistry could play in the near future for a sustainable development.
Keywords: flash chemistry; flow chemistry; green chemistry; microreactor technology; sustainable synthesis